THE ABSORBER LAYER VARIATION EFFECT ON THE PERFORMANCE OF FASNX3-BASED PEROVSKITE SOLAR CELL - Ramaputra, Setianto
The development of third-generation solar cell technology is currently accelerating and proliferating, including perovskite solar cells. The presence of lead, which is commonly found in perovskite solar cells, hinders the development of this type of solar cell to the mass production stage. The critical necessity to eliminate harmful lead from extensively utilized metal halide perovskite solar cells (PSCs) necessitates the creation of effective and dependable lead-free perovskite alternatives. This study examines the performance of lead-free, hybrid organic-inorganic Sn-based PSCs utilizing SCAPS-1D and VASP. The solar cell architecture used in this study is FTO/TiO?/FASnX?/PTAA/Au (X = Br, Cl). The perovskite layer material structure is based on FASnI3, which is then modified by replacing the halogen anions with Br and Cl. Optimization was carried out to achieve better material structure and energy bandgap. The results of the structural optimization are used to analyze the overall performance of the perovskite solar cells, particularly the power conversion efficiency of the solar cells. Based on the research findings, it shows that the FASnI3 perovskite layer has a better power conversion efficiency compared to FASnBr3 and FASnCl3, with the highest efficiency being 29.02%, making it a good contender for improving perovskite solar cell performance. This work advances current experimental initiatives by suggesting an innovative device architecture and certain parameters, thereby offering an original strategy for optimizing the design of lead-free perovskite solar cells and facilitating future research in this field. Keywords: Absorber layer, lead-free, Sn-based perovskite solar cell, SCAPS 1-D, solar cell performance.